2004
DOI: 10.1002/pds.977
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis with HMG‐CoA reductase inhibitors and gemfibrozil combination therapy

Abstract: Rhabdomyolysis is a rare, serious side effect of statin monotherapy and of statin-fibrate combination therapy. Clinicians need to remain cognizant of this potential adverse event and discuss signs and symptoms of muscle toxicity with patients in order improve the benefits-to-risks of treating dyslipidemia with statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
4
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 16 publications
1
85
4
1
Order By: Relevance
“…155 However, these figures are likely to underestimate the risk both because they are based on voluntary reporting by healthcare professionals, and because they use as the denominator the number of prescriptions, not the number of individuals using the medication. 152 Rates of fatal and non-fatal rhabdomyolysis reported to the US FDA's postmarketing database were also similar, at less than one case per million prescriptions, for all statins except for cerivastatin 156 ( Table 28). More than 80% of cases reported for each drug when taken as monotherapy resulted in hospitalisation for renal failure and dialysis, and 10% resulted in death.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…155 However, these figures are likely to underestimate the risk both because they are based on voluntary reporting by healthcare professionals, and because they use as the denominator the number of prescriptions, not the number of individuals using the medication. 152 Rates of fatal and non-fatal rhabdomyolysis reported to the US FDA's postmarketing database were also similar, at less than one case per million prescriptions, for all statins except for cerivastatin 156 ( Table 28). More than 80% of cases reported for each drug when taken as monotherapy resulted in hospitalisation for renal failure and dialysis, and 10% resulted in death.…”
mentioning
confidence: 90%
“…More than 80% of cases reported for each drug when taken as monotherapy resulted in hospitalisation for renal failure and dialysis, and 10% resulted in death. 156 This demonstrates that, although rhabdomyolysis is a rare event, it presents a significant safety issue for statin drugs even when taken as monotherapy; the risk is increased when statins are used in combination with gemfibrozil (Table 29).…”
mentioning
confidence: 99%
“…0.3 per million prescriptions; rosuvastatin, data not available). 65 A more accurate estimate of the incidence of 66 Prescription data were used to identify a cohort of 252,460 lipidlowering drug users from 11 health plans across the USA between January 1998 and June 2001. Hospital data were then used to establish how many of the cohort were admitted to hospital with a diagnosis of rhabdomyolysis.…”
Section: Moderate-dose Statinsmentioning
confidence: 99%
“…Despite such a low incidence rate, certain drugs such as amiodarone that this patient has been taking to control ventricular rate could increase the risk of rhabdomyolysis when combined with statins [16]. In fact, a review of the United States Food and Drug Administration post-marketing database of rhabdomyolysis (CK 10,000) showed that, of 866 cases reported between 1987 and 2001, 44% were related to combination therapy, as compared with statins alone [22]. The rosuvastatin specification mention that according to the FDA, the risk of myopathy during rosuvastatin therapy may be increased in Asian Americans because Asians appear to process the drug differently, half the standard dose can have the same cholesterol-lowering benefit in those patients, though a full dose could increase the risk of side-effects, which was indicated by the drug's manufacturer, AstraZeneca.…”
Section: Discussionmentioning
confidence: 99%